2018
DOI: 10.1155/2018/7218102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Exercise Training Program on Physical Function in Institutionalized Frail Elderly

Abstract: With the increase in life expectancy, the Brazilian elderly population has risen considerably. However, longevity is usually accompanied by problems such as the loss of functional capacity, cognitive decline, frailty syndrome, and deterioration in anthropometric parameters, particularly among those living in long-term care facilities. This randomized controlled trial aimed to verify the effects of exercise training on biochemical, inflammatory, and anthropometric indices and functional performance in instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
55
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 48 publications
12
55
1
3
Order By: Relevance
“…Because the prevalence of frailty varies widely depending on the test, this study used four different tools to assess frailty. The results agree with a previous study that showed a lower prevalence of frailty according to Fried's frailty phenotype after an exercise program in older adults in a long‐term care facility in Brazil . Further, the significant increase in the IG and decrease in the CG of the SPPB score that we report agrees with another study that performed resistance training in LTNHs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Because the prevalence of frailty varies widely depending on the test, this study used four different tools to assess frailty. The results agree with a previous study that showed a lower prevalence of frailty according to Fried's frailty phenotype after an exercise program in older adults in a long‐term care facility in Brazil . Further, the significant increase in the IG and decrease in the CG of the SPPB score that we report agrees with another study that performed resistance training in LTNHs.…”
Section: Discussionsupporting
confidence: 93%
“…According to the SOF index, the prevalence of frailty tended to be lower in the IG, but the differences were not significant. Therefore, these results are consistent with results published in recent studies that seem to indicate physical exercise could play an important role in reducing frailty . However, more research is needed to determine an optimum program to tackle frailty in LTNHs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations